A monocentric, randomized, double-blind, controlled crossover trial of nasturtium (Tropaeolum majus) on the lipid regulator prostaglandin E2 - Herz, Corinna; Frei, Linda; Tran, Hoai T. T.; Claßen, Sophie; Spöttel, Jenny; Krell, Mareike; Hanschen, Franziska S.; Arvandi, Marjan; Binder, Nadine; Schreiner, Monika; Rohn, Sascha; Lamy, Evelyn (Frontiers in Nutrition, 2023)
Scope: As prostaglandin E2 (PGE2) has important roles in physiological and inflammatory functions, a double-blind randomized controlled crossover study to investigate the potential of nasturtium (Tropaeolum majus) for modulating PGE2 was conducted, aiming at clarifying the role of benzyl isothiocyanate (BITC). As secondary parameters leukotriene 4 (LTB4), and cytokine release (tumor necrosis factor alpha, TNF- interleukins IL-1, IL-10, and IL-12) were quantified.Methods and Results: 34 healthy female participants consumed 1.5 g nasturtium containing BITC, (verum) or no BITC (control) twice a day for 2 weeks each. Nasturtium intervention resulted in an increase in mean PGE2 levels in serum samples (verum: 1.76-fold, p ≤ 0.05; control: 1.78-fold, p ≤ 0.01), and ex vivo stimulated PBMC (verum: 1.71-fold, p ≤ 0.01; control: 1.43-fold). Using a pre-topost responder analysis approach, 18 of 34 subjects showed a > 25% PGE2 increase in serum, while it was > 25% decreased for 9 subjects (stimulated PBMC: 14 and 8 of 28, respectively). Under the selected conditions, the BITC content of nasturtium did not affect the observed changes in PGE2. Verum intervention also increased mean LTB4 serum level (1.24-fold, p≤ 0.01), but not in LPS stimulated PBMC, and significantly increased TNF-α release in stimulated PBMC after 3 h (verum: 1.65-fold, p= 0.0032; control: 1.22-fold, p=0.7818). No change was seen in the anti-inflammatory cytokine IL-10, or the pro-inflammatory cytokines IL-1β, and IL-12.In contrast to the previously reported in vitro results, on average, LPS activated PBMC and serum from both groups showed increased PGE2 levels. Further analyses suggest that PGE2 release after intervention could possibly depend on the baseline PGE2 level. Identification of phenotypes that respond differently to the nasturtium intervention could be useful to establish personalized approaches for dosing phytopharmaceuticals medicines.